Exploring Qur’anic Stance on Mental Health: An Analytical Review - Tahir, Dr. Muhammad; Zubairi, Dr. Sami Ullah (University of Wah Journal of Social Sciences, 2019)
In recent decades, there is a massive increase in mental health issues worldwide. Muslim communities seemingly facing mental health issues at an alarming rate. Traditionally, mental health is an important issue among public health issues. Therefore, religions and social sciences reflect upon its various aspects. Necessarily, religion and mental health have had deep connections and relationships throughout human history. All the Abraham religions provide awareness and guidance for mental health issues from a religious domain. Thus, mental health has become a subject of more attention for religious scholars too, which creates a current need for addressing this issue from an Islamic perspective. Islam, being a complete code of life for Muslims, provides a holistic overview of mental health issues for the development of sound masses in society. Islamic teachings describe a vibrant coping mechanism to deal with mental illnesses, psychological problems, and uncertain conditions of life. The present study draws attention specifically on mental health and well-being from the Qur’anic discourse to present possible solutions within an Islamic domain. The presented understanding of Qur’anic stance on mental health incorporates with human needs and requirements to provide a practical framework for the improvement of general health conditions in the contemporary Muslim world, multi-cultural societies, and the multi-religious Western world. The study employs a qualitative content analysis methodology to discuss the topic from the verses of the Qur’an. The current endeavor will be beneficial for the welfare of humanity globally. However, further exploration is needed to integrate the Qur’anic instructions in Muslim culture and society.